Grain yield of maize varieties with yellow endosperm and earliness for Mexican highlands. - Espinosa-Calderón, Alejandro (2013)
The objective in this work was to evaluate the grain yield capacity of yellow grain maize varieties developed in The Cuautitlan Faculty of Superior Studies, of the Autonomous National University of Mexico (FESC-UNAM), and the National Institute for Forestry, Agricultural and Livestock, Research (INIFAP). Two experiments were planted in two locations; one in the CEVAMEX, in Saint Lucia of Prias and another at the FESC-UNAM, compared to white grain and yellow commercial control groups; both were planted mid June, 2010. Thirteen maize varieties were evaluated in each experiment under a randomized complete block design with three replications. The site of CEVAMEX had the best grain yielding, 5887 kg/ha, and was superior (p ≤ 0.05) to the experiment of FESC-UNAM (3799 kg/ha). The best grain yielding va-rieties were ORO ULTRA UNAM C (6913 kg/ha), V-55 A (6284 kg/ha), V-53 A (6035 kg/ha) and A V-54 (5405 kg/ha).